IMPROVING STUDENTS' PRONUNCIATION THROUGH WESTERN MOVIE MEDIA - Mohammad Syarif Hidayatullah (LP2M IAIN Sultan Amai Gorontalo, 2018)
This research aims to determine how does Western Movie Media improve the students’ pronunciation. This Research uses a Class Action Research (CAR). The subject of this research is the four semester of English Education at IAIN Sultan Amai Gorontalo. There were 30 students consisting of 10 male students and 20 female students. The instruments of data collection were observation sheet on teacher’s and students’ activity, and pronunciation test. The action research carried out in three cycles. There were 16 students got 75 in the first cycle, second cycle increased 18 students, and in third cycle 28 students.